Clinical and Basic Evaluation of the Effects of Upregulated TNFAIP3 Expression on Colorectal Cancer. (18th August 2022) - Li, Jinhe; Ren, Shuang; Zhang, Yuhua; Wu, Bingbing; He, Meng; Shan, Zhen; Liu, Yang; Wang, Yuejing
Abstract : Objective. To assess the TNFAIP3 and nuclear factor κ B (NF κ B) protein expressions in colorectal cancer (CRC) tissue and to analyze the association of these proteins with the clinical pathological characteristics of CRC. Methods. The following methods should be used in clinical trials: information collection and immunohistochemical methods. The following methods are used for cell experiment: cell transfection, CCK8 detection method, transwell experiment, and western blot experiment. Explore the TNFAIP3 expression in CRC cells, and assess the effect of upregulated TNFAIP3 expression on CRC cell proliferation, invasion, and migration. In clinical experiment, we selected the tumor tissues of 39 CRC patients as our experimental samples. We also collected corresponding patient demographics, such as sex, age, cell differentiation, tumor type, and lymph node metastasis. We also analyzed the TNFAIP3 and NF κ B protein expressions in 20 experimental and 20 control samples and evaluated potential correlations between these two proteins and clinical pathological characteristics of CRC. For basic experiment, we established CRC cell lines with elevated TNFAIP3 expression and then randomly divided the cells into three groups, namely, TNFAIP3, NS, and Con groups. Using the transwell and CCK8 methods, we detected the CRC migration abilities and cell proliferation, respectively. We also employed western blot analysis to assess protein expression in the three groups. Results. NF κ B was highly expressed, and TNFAIP3 was scarcely expressed in the experimental group versus control. The expression of both these proteins were strongly related to the degree of tumor differentiation (P < 0.05 ). The TNFAIP3 and NF κ B protein expressions were significantly associated with lymph node metastasis and tumor differentiation (P < 0.05 ). For basic experiment, compared to the Con and NS groups, TNFAIP3 protein expression levels, cell proliferation, invasion, and migration were significantly increased in the TNFAIP3 group (P < 0.05 ). Conclusion. TNFAIP3 overexpression strongly inhibited CRC proliferation, invasion, and migration. Enhanced NF κ B protein expression in CRC tissues was associated with elevated malignant degree, metastasis, and TNFAIP3 protein expression in patients who demonstrated high malignant degree and metastasis. Our evidences suggest the promising potential of utilizing TNFAIP3 and NF κ B as important reference indices for determining the prognostic outcome of CRC. Furthermore, we revealed that TNFAIP3 overexpression inhibited CRC cell proliferation, invasion, and migration.